Preparation of carbon-coated magnetic nanocomposites under inert atmosphere and at low temperature. (15th January 2017) - Zuo, Shangshang; Bai, Hongxia; Han, Qi; Liao, Hong-Gang; Gu, Hongbo; Chen, Zuofeng
Abstract: We report here that carbon-coated magnetic nanocomposites can be prepared by calcination of the mixture of ferric nitrate (Fe(NO3 )3 ) and hydroxyethyl cellulose under argon atmosphere (without hydrogen) and at low temperature (400 °C). The magnetic property of the as-prepared samples can be tuned by simply varying the calcination temperature, the flow rate of argon, the retention time, and the heating rate. The characterization of these samples by XRD, FTIR, TEM and XPS reveals that their magnetic property is closely related with the contents of Fe3 O4 and Fe2 O3 in these samples. The proposed mechanism indicates that the reduction of the spatial and temporal contact of the decomposed Fe intermediates with the NO2 and O2 byproducts would be favorable for the formation of Fe3 O4, leading to the higher saturation magnetization of the samples. Graphical abstract: We report that carbon-coated magnetic nanocomposites can be prepared by calcination of the mixture of ferric nitrate (Fe(NO3 )3 ) and hydroxyethyl cellulose under benign calcination conditions (argon atmosphere, 400 °C). The magnetic property of the as-prepared samples can be tuned by simply varying the calcination temperature, the flow rate of argon, the retention time, and the heating rate, which would have important implication for the use of Fe(NO3 )3 as iron source for future preparation of carbon-coated magnetic nanocomposites with high saturation magnetization. Highlights: The magnetic nanocomposites were prepared by calcining Fe(NO3 )3 and carbon precursor mixture in Ar and at low temperature. The magnetic property was tuned by varying calcination temperature, gas flow rate, retention time, and heating rate. The saturation magnetization relies on the spatial and temporal contact of Fe intermediates with NO2 and O2 byproducts.